Global Tracking Control of Quadrotor VTOL Aircraft in Three-Dimensional Space - Duc Khac Do (Institute of Advanced Engineering and Science, 2014)
This paper presents a method to design controllers that force a quadrotor vertical take-off and landing (VTOL) aircraft to globally asymptotically track a reference trajectory in three-dimensional space. Motivated by the vehicle's steering practice, the roll and pitch angles are considered as immediate controls plus the total thrust force provided by the aircraft's four rotors to control the position and yaw angle of the aircraft. The control design is based on the newly introduced one-step ahead backstepping, the standard backstepping and Lyapunov's direct methods. A combination of Euler angles and unit-quaternion for the attitude representation of the aircraft is used to obtain global tracking control results. The paper also includes a design of observers that exponentially estimate the aircraft's linear velocity vector and disturbances. Simulations illustrate the results.